Establishing the relevance of the Ubuntu philosophy in social work practice: Inspired by the Ubuntu World Social Work Day, 2021 celebrations and the IFSW and IASSW's (2014) Global Definition of Social Work - Chigangaidze, Robert K; Mafa, Itai; Simango, Tapiwanashe G; Mudehwe, Elia (SAGE Publications, 2022)
The philosophy of Ubuntu has gained momentum in the social work fraternity to the extent that the theme for the World Social Work Day, 2021 celebrations read, ‘Ubuntu: I am Because We are – Strengthening Social Solidarity and Global Connectedness’. Through the use of a qualitative research approach, underpinned by a document analysis method, the article initiates a discourse which expounds on the philosophy through the lenses of the IFSW and IASSW 2014 Global Definition of Social Work. Substantially, it proffers justifications that cement the relevance of the Ubuntu philosophy in both the practice and theoretical frameworks of social work.